Cover Feature: A Natural Transporter of Silicon and Carbon: Conversion of Rice Husks to Silicon Carbide or Carbon‐Silicon Hybrid for Lithium‐Ion Battery Anodes via a Molten Salt Electrolysis Approach (Batteries & Supercaps 12/2019). Issue 12 (3rd December 2019) - Zhao, Zhuqing; Xie, Hongwei; Qu, Jiakang; Zhao, Haijia; Ma, Qiang; Xing, Pengfei; Song, Qiushi; Wang, Dihua; Yin, Huayi
Abstract : The Cover Feature shows the natural cycle of harvesting silicon from soil and carbon from the air by using rice husks. A molten salt electrolysis approach is able to convert the rice husks to SiC/C or Si/C composites that are used as high‐performance anode in lithium‐ion batteries.More information can be found in the Article by Z. Zhao et al .